Impact dissipation of EPS boost foam - Lee, Tessa Si Min (2018)
Expanded polystyrene (EPS) is a material commonly used to make the inner liner of a protective bicycle helmet due to its excellent performance and lightweight characteristics. This final year project aims at understanding the behaviour of different densities of EPS foam under impact and developing a EPS-honeycomb hybrid structure in an effort to enhance impact dissipation properties of EPS foam for bicycle helmet liner applications. There are 3 different types of EPS foam samples manufactured for mechanical testing. Pure EPS foam samples, HC samples (honeycomb layer in the middle of EPS sample) and FHC samples (honeycomb layer at the top of EPS sample). For all 3 types of samples, they are categorised by 3 groups of density range. Category A (29g/L-37g/L), Category B (38g/L-46g/L), Category C (52g/L – 65g/L). Before manufacturing specimens for testing, several manufacturing trials have been carried out to understand and fine-tune the conditions and procedure for producing the various expanded polystyrene foam samples. After understanding the process well, specimens were manufactured for mechanical testing. Impact tests were carried out for the manufactured EPS foam samples of varying densities first, to observe and identify the relationship between density and energy absorption property of the foam. Hardness test was also carried out to identify the correlation between hardness and density. Peak load and energy absorbed after impact were also analysed in this project. Results were compared between pure EPS foam samples and EPS-honeycomb hybrid samples with different honeycomb orientation, in various density categories. It can be concluded that the effect of density has a significant influence on the mechanical behaviour of the EPS samples. Size of pre-expanded beads could possibly influence the energy absorption capability of the EPS foam by controlling the allowance of deformation. The EPS-honeycomb hybrid structure with the middle configuration showed an improvement in energy absorption capacity, hence it has potential in improving the impact dissipation property of the EPS foam liner.